Rational Hybrid Analytical Model for Steel Pipe Rack Quantification in Oil & Gas Industries - Manoharan Rajalingam; Amit Srivastava (Civil Engineering Journal, 2020)
The objective of this work is to develop an analytical model to overcome the shortfalls in current engineering practices that are being used to estimate the pipe rack steel quantities during the pre-bid engineering phase in Oil & Gas industries. The research methodology consists of performing data analysis of past projects and devising a new system by developing suitable structure formulation techniques, loading system creation, structural stability analysis and LRFD design calculations, along with steel quantification procedures, which are completed in a single run. Then this rational hybrid analytical model is applied to examine a real-time project pipe rack structure module. As research findings, the results of the analytical model are compared with the outcome of both the conventional methods as well as the bench mark detailed engineering calculations. It is found that the quantity obtained using the new method is extremely close to the detailed engineering quantity with the least time consuming. Hence, this novel analytical model has proved to be a boon to structural engineers working in Oil and Gas industries since the crux of pre-bid engineering is to process voluminous data and calculate the quantities more precisely within a shorter time frame to be a successful bidder.